Dysphonia and odynophagia: a presentation of late syphilis - Barreto, Joana (2023)
Syphilis is known to be “the great imitator”, as the clinical history is often treacherous and the clinical spectrum of signs and symptoms is extremely extensive, making diagnosis particularly challenging. We present the case of a 69-year-old man with symptoms of hearing loss, dysphonia and odynophagia for 3 months. Associated with this, he had pruritus with generalized erythema and cutaneous desquamation, changes in visual acuity and nocturnal hypersudoresis. He had a history of smoking and alcoholism and had denied unprotected sexual contact for 10 years. In the oropharynx, flat, whitish lesions were observed on the soft palate. Laryngoscopy showed alterations, with areas of leukoplakia in both vocal cords, ventricular bands and posterior commissure. The analytical study was compatible with the diagnosis of syphilis. The patient complied with the recommended treatment and presented resolution of the complaints and lesions observed.